1977
DOI: 10.1063/1.434183
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-19 FT–NMR studies of CF3-containing systems dissolved in smectic liquid crystal solutions

Abstract: Articles you may be interested inThe dynamical behavior of a small probe molecule dissolved in a nematic liquid crystal studied by NMR J. Chem. Phys. 78, 1712 (1983; 10.1063/1.444956 19F shielding anisotropies of the fluoromethanes obtained from NMR studies in a smectic liquid crystal solution J. Chem. Phys. 66, 989 (1977); 10.1063/1.434010 Deuterium magnetic resonance study of a smectic liquid crystalThe fluorine-19 shielding anisotropies of CFJCI, CF 3 Br, CFJI, and CF J CCl 3 have been determined from analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1978
1978
1983
1983

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…It has been shown that this method of temperature variation can lead to serious discrepancies when compared with the results obtained by use of the smectic phase in which the ordering parameter 5ZZ can be changed by means of a sample orientation change instead of a temperature change. 43 However, in the present study, it has been checked on one compound (PtBu)4 that the value obtained by use of a smectic phase is in good agreement with the one obtained by use of a nematic phase (145 vs. 167 ppm).…”
Section: Discussion Of the Resultssupporting
confidence: 70%
“…It has been shown that this method of temperature variation can lead to serious discrepancies when compared with the results obtained by use of the smectic phase in which the ordering parameter 5ZZ can be changed by means of a sample orientation change instead of a temperature change. 43 However, in the present study, it has been checked on one compound (PtBu)4 that the value obtained by use of a smectic phase is in good agreement with the one obtained by use of a nematic phase (145 vs. 167 ppm).…”
Section: Discussion Of the Resultssupporting
confidence: 70%